2014
DOI: 10.5539/ijbm.v10n1p144
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Quality of Innovation in Cloud Computing Adoption

Abstract: The emergence of cloud computing is quickly redefining the information technology (IT) and business landscape. Cloud computing involves delivery of IT infrastructure, software and platforms as a service to the end users. This IT acquisition model saves organizations from huge capital expenditures on IT and the burden of keeping a huge IT department to provide system support. Cloud computing as an IT innovation is steadily generating a lot of interest within IT innovation researchers and practitioners. Extant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…This can be supported by the finding of [65] where the researcher found that perceived benefits has positive impact on Cloud adoption decision. The perceived benefits of Cloud Computing may go beyond cost savings such as providing new services that could not be provided before [64]. Awosan in [66] found that increased focus on core business is a major reason for adopting the Cloud.…”
Section: Business Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be supported by the finding of [65] where the researcher found that perceived benefits has positive impact on Cloud adoption decision. The perceived benefits of Cloud Computing may go beyond cost savings such as providing new services that could not be provided before [64]. Awosan in [66] found that increased focus on core business is a major reason for adopting the Cloud.…”
Section: Business Contextmentioning
confidence: 99%
“…soft financial analysis and hard financial analysis) in this context have high values which represent the importance of business concerns on the adoption decision. Since Cloud Computing is a new way of delivering and dealing with computing services not a new technology [64], many healthcare organisations evaluate the use of Cloud Computing from a strategic point view. This has been shown by making soft financial analysis as the most important factor among other factors.…”
Section: Business Contextmentioning
confidence: 99%
“…If the top of the organization is highly sensitive to information security issues, so this government is likely to slow the process of adoption of cloud computing. In addition, if an organization level control of resources is very sensitive, and the resources of his own department transfer to the other departments under a unified management may weaken the control of resources department leadership ability, and even undermine the power of sector management leadership, then such governments may resist cloud computing technology (Oredo & Njihia, 2014).…”
Section: ) Top Management Supportmentioning
confidence: 99%
“…The adoption behavior of the E-government cloud must be influenced by the size and complexity of information resources. The arrangement of information personnel and the transformation of the function are the problems that the organization is required to solve (Oredo & Njihia, 2014). Moreover, the number of the original systems and the degree of difficulty for IS migration determine whether to adopt cloud or not.…”
Section: ) the Scale And Complexity Of Information Resourcesmentioning
confidence: 99%
See 1 more Smart Citation